2021
DOI: 10.1155/2021/6672158
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Analysis on a Three-Dimensional Wavy Flow of Eyring–Powell Nanofluid: A Comparative Study

Abstract: The thermal management of a system needs an accurate and efficient measurement of exergy. For optimal performance, entropy should be minimized. This study explores the enhancement of the thermal exchange and entropy in the stream of Eyring–Powell fluid comprising nanoparticles saturating the vertical oriented dual cylindrical domain with uniform thermal conductivity and viscous dissipation effects. A symmetrical sine wave over the walls is used to induce the flow. The mathematical treatment for the conservatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…e Prandtl number and nanoparticle volume fraction have opposite impacts on the thermal field [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…e Prandtl number and nanoparticle volume fraction have opposite impacts on the thermal field [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…eir outcomes found that the Eckert number enhanced the velocity profile; however, the thermal Grashof number opposes the temperature profile. [12] discussed the entropy mechanism of a three-dimensional wavy flow using Eyring-Powell nanofluid. Mathematical and physical modeling is performed based on the lubrication approach.…”
Section: Recent Advances In Multiphase Flows In Engineeringmentioning
confidence: 99%
“…Sangeetha and De [22] analyzed the bioconvection in nanoliquid stream with viscous losses and Ohmic heating. Riaz et al [23] presented a comparative analysis of entropy assessment on a (3-D) wavy stream of Eyring-Powell nanoliquid.…”
Section: Introductionmentioning
confidence: 99%